Idea And Literary Interpretation in the Lyrics of Erkin Vahidov - Baltayeva Z.Sh (Genius Journals, 2023)
The article examines the idea and literary interpretation of Erkin Vahidov's lyrics, the uniqueness of the poet's style of expression, and the artistic function of words. It theoretically summarizes the demonstration of the nature of the creator, the level of the image object, the principles of poetic research of life, the nature of aesthetic perception, the author's skills and evaluation criteria.
Keywords: Lyrics; literary interpretation; style of expression